Occurrence and impact of domestic violence and abuse in gay and bisexual men: A cross sectional survey. (January 2017) - Bacchus, LJ; Buller, AM; Ferrari, G; Peters, TJ; Devries, K; Sethi, G; White, J; Hester, M; Feder, GS
Summary: This cross-sectional survey measured adult experience and perpetration of negative and potentially abusive behaviours with partners and its associations with mental and sexual health problems, drug and alcohol abuse in gay and bisexual men attending a UK sexual health service. Of 532 men, 33.9% (95% CI: 29.4-37.9) experienced and 16.3% (95% CI: 13.0-19.8) reported carrying out negative behaviour. Ever being frightened of a partner (aOR 2.5; 95% CI: 2.0–3.1) and having to ask a partner's permission (aOR 2.7; 95% CI: 1.6–4.7) were associated with increased odds of being anxious. There were increased odds of cannabis use in the last 12 months amongst men who reported ever being physically hurt (aOR 2.4; 95% CI: 1.7–3.6). Being frightened (aOR 2.2; 95% CI: 1.5–3.2), being physically hurt (aOR 2.3; 95% CI: 1.4–3.8), being forced to have sex (aOR 2.5; 95% CI: 1.3–4.9) and experiencing negative behaviour in the last 12 months (aOR 1.7; 95% CI: 1.2–2.5) were associated with increased odds of using a Class A drugs in the last 12 months. Sexual health practitioners should be trained with regards to the risk indicators associated with domestic violence and abuse, how to ask about domestic violence and abuse and refer to support.